ANALISIS NILAI PENDIDIKAN AGAMA ISLAM DALAM NOVEL CINTA SUBUH KARYA ALII FARIGHI PERSPEKTIF TAKSONOMI BLOOM - Febianti, Karina; Shomary, Sudirman (UIR Press, 2024)
This research is motivated by the importance of Islamic religious education values in human life and forming good Islamic religious education in terms of affective, cognitive, and psychomotor. The problems in this research are: How are the values of Islamic religious education in the aspects of belief, worship, and moral aspects contained in the novel Cinta Subuh by Alii Farighi from the perspective of Bloom's taxonomy? The purpose of this study is to describe and analyze the data of Islamic religious education values in the novel Cinta Subuh by Alii Farighi from the perspective of Bloom's taxonomy. The theory used in this research refers to the theory of Islamic religious education by Muhammad Ali (2013) and Bloom's taxonomy theory by Fauzi (2017), Suliswiyadi (2020), Kartini et al. This research data is in the form of all sentence quotation data in the novel Cinta Subuh by Alii Farighi which contains the value of Islamic religious education related to Bloom's taxonomy perspective. This research approach uses a qualitative approach, the method used is descriptive method using hermeneutic techniques and analyzed using content analysis techniques. The results of this study conclude that there is a value of Islamic religious education in the novel Cinta Subuh by Alii Farighi, namely 1) The value of faith has 11 data related to the affective and cognitive domains. 2) The value of worship has 22 data related to the affective, cognitive and psychomotor domains. 3) Moral values have 21 data related to the affective and cognitive domains.